2015
DOI: 10.1111/cpf.12318
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intramuscular differences in training‐induced hypertrophy of the quadriceps femoris: association with muscle activation during the first training session

Abstract: The purpose of this study was to examine whether inter- and intramuscular differences in hypertrophy induced by resistance training correspond to differences in muscle activation during the first training session. Eleven young men completed 12 weeks of training intervention for knee extension. Before and after the intervention, T1-weighted magnetic resonance (MR) images were recorded to determine the volume and anatomical cross-sectional area (CSA) along the length of the individual muscles of the quadriceps f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
10
24
0
Order By: Relevance
“…Regarding the region-specific analysis, there was a tendency for a greater hypertrophic effect at the distal compared with the proximal site. This is similar to previous research indicating that the increase in individual muscle sizes is somewhat greater at the distal site (Narici et al 1996;Seynnes et al 2007;Wakahara et al 2017). The justification for assessing potential differences in the hypertrophic response across different anatomical sites along the muscle stems from the inherent differences in the characteristics of the training devices.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the region-specific analysis, there was a tendency for a greater hypertrophic effect at the distal compared with the proximal site. This is similar to previous research indicating that the increase in individual muscle sizes is somewhat greater at the distal site (Narici et al 1996;Seynnes et al 2007;Wakahara et al 2017). The justification for assessing potential differences in the hypertrophic response across different anatomical sites along the muscle stems from the inherent differences in the characteristics of the training devices.…”
Section: Discussionsupporting
confidence: 86%
“…This study is the first to show different hypertrophic responses of individual QF muscle after ECC vs CON training. However, it should be noted that a similar result in terms of greater hypertrophy of RF than the vasti has been reported after single‐joint knee extension training using a conventional weight lifting/lowering model (ie, involving both CON and ECC contractions), or even after CON‐only knee extension training, but not after ISO knee extension training (ie, equivalent hypertrophy among QF muscles) . These findings and the current result together imply that (a) dynamic (ECC and/or CON) but not static (ISO) knee extension training results in pronounced hypertrophy in RF and (b) an ECC stimulus is not a requisite but promotes muscle hypertrophy.…”
Section: Discussionsupporting
confidence: 86%
“…One important limitation that should be acknowledged is regarding the use of ultrasound measures to assess muscle hypertrophy, especially in the quadriceps muscles. Ultrasound gives only an estimated MT in a specific point, and previous studies have shown considerable inter-and intramuscular differences in training-induced hypertrophy [31]. Therefore, its results cannot precisely define hypertrophy of the whole muscle.…”
Section: Back Squat Group (N = 12)mentioning
confidence: 98%